Línea sur 5 : foreign policy journal, may / aug 2013
Línea Sur, the Foreign Policy Journal of the Ministry of Foreign Affairs and human mobility, receives submissions for publication continuously. Articules must conform to the publication guidelines of the journal and elaborate on themes related to the field of international relations, preferably as related to Ecuador.